Managing Environmental and Social Risks in Development Policy Financing - Independent Evaluation Group (World Bank, Washington, DC, 2015)
Effective environmental and social risk management in development policy financing (DPF) is central to achieving the World Bank’s goals of ending extreme poverty and promoting shared prosperity in a sustainable manner. If the World Bank is supporting far-reaching member country reforms that are intended to contribute to the twin goals, then it should seek to understand the impact of those reforms on the poor. It should also ensure that the country’s natural capital and long-term growth prospects will not be undermined. The objective of this learning product is therefore to assess the application of the elements of the World Bank operational policy (OP 8.60) governing DPF related to the implementation of the environmental and social risk management requirements of the policy, and identify lessons learned and good practices. The focus of the study is on Bank actions, policies, procedures, and guidance for environmental and social risk management, based largely on a desk-based portfolio review of a large, random sample of development policy operations (DPOs), complemented by assessment of other relevant documents, and interviews with key stakeholders. This approach requires the Bank to determine whether specific policies supported by a DPO are likely to have significant poverty and social or environmental effects. The Bank emphasized the potential of OP 8.60 to promote positive environmental and social development from the time the policy was approved in 2004.